Variations on a theme: Genomics of sex determination in the cichlid fish Astatotilapia burtoni. (December 2016) - Böhne, Astrid; Wilson, Catherine; Postlethwait, John; Salzburger, Walter
Abstract Background Sex chromosomes change more frequently in fish than in mammals or birds. However, certain chromosomes or genes are repeatedly used as sex determinants in different members of the teleostean lineage. East African cichlids are an enigmatic model system in evolutionary biology representing some of the most diverse extant vertebrate adaptive radiations. How sex is determined and if different sex-determining mechanisms contribute to speciation is unknown for almost all of the over 1, 500 cichlid species of the Great Lakes. Here, we investigated the genetic basis of sex determination in a cichlid from Lake Tanganyika, Astatotilapia burtoni, a member of the most species-rich cichlid lineage, the haplochromines. Results We used RAD-sequencing of crosses for two populations ofA. burtoni, a lab strain and fish caught at the south of Lake Tanganyika. Using association mapping and comparative genomics, we confirmed male heterogamety inA. burtoni and identified different sex chromosomes (LG5 and LG18) in the two populations of the same species. LG5, the sex chromosome of the lab strain, is a fusion chromosome inA. burtoni. Wnt4 is located on this chromosome, representing the best candidate identified so far for the master sex-determining gene in our lab strain ofA. burtoni . Conclusions Cichlids exemplify the high turnover rate of sex chromosomes in fish with two different chromosomes, LG5 and LG18, containing major sex-determining loci in the two populations ofA. burtoni examined here. However, they also illustrate that particular chromosomes are more likely to be used as sex chromosomes. Chromosome 5 is such a chromosome, which has evolved several times as a sex chromosome, both in haplochromine cichlids from all Great Lakes and also in other teleost fishes.